Efektivitas Manajemen Diri dan Pemberdayaan terhadap Luaran Psikososial dan Klinis Pasien Hemodialisis Dewasa - Cokorda Gede Bagus Muladhara Cakra Kailasa; I Gusti Agung Istri Mahaiswari; Anak Agung Ngurah Agung Bagus Tri Laksamana Putra; I Komang Surya Prawira Tangkas (Aesculapius Medical Journal, 2026)
Abstract Effectiveness of Self-Management and Empowerment on Psychosocial and Clinical Outcomes of Adult Hemodialysis Patients Chronic kidney disease (CKD) and end-stage renal disease (ESRD) are major global health problems, particularly among patients undergoing hemodialysis. Patients’ ability to manage their condition is strongly influenced by self-management and empowerment interventions, which aim to improve psychosocial outcomes such as self-efficacy and self-care knowledge, as well as clinical outcomes including blood pressure control and weight management. This systematic review aimed to evaluate the effectiveness of self-management and empowerment interventions on psychosocial and clinical outcomes in adult hemodialysis patients by synthesizing existing evidence, comparing findings between randomized controlled trials (RCTs) and non-RCTs, and assessing the potential for publication bias. Literature searches were conducted in PubMed, Scopus, and Cochrane CENTRAL according to predefined inclusion criteria. Study screening and data extraction were performed using Rayyan, risk of bias was assessed with RoB 2.0 for RCTs and ROBINS-I for non-RCTs, while statistical analyses were carried out using Jamovi, including subgroup analyses, sensitivity analyses, and publication bias testing. A total of eight studies met the inclusion criteria. The results indicated that self-management and empowerment interventions produced moderate improvements in self-efficacy (Cohen’s d = 0.58) and favorable clinical outcomes, including a mean reduction in blood pressure of 5.6 mmHg. Subgroup analyses showed no significant differences between RCTs and non-RCTs (p = 0.15), sensitivity analyses confirmed the robustness of the findings, and publication bias testing revealed no significant bias. This review supports the effectiveness of self-management and empowerment interventions in improving psychosocial and clinical outcomes among hemodialysis patients, and recommends future research with long-term follow-up, standardized outcome measures, and high-quality RCTs to confirm effectiveness across more diverse patient populations. Keywords: Chronic Kidney Disease, Hemodialysis, Self-Management, Empowerment, Self-Efficacy.